Fair Water Pricing For Sustainable Management Of Available Water In India - Pooja Mehra, Saurabh Verma, Gurinderjit Kaur (International Journal of Advanced Science and Technology, 2020)
Adequate availability of freshwater will be the most challenging issue of the 21st centurybecause of its scarcity. Water is regarded as a free good and a gift of nature, but it involves amassive cost for its collection, storage, groundwater pumping and delivery to potential users.Presently its cheap availability to farmers, domestic user and individuals resulting enormous lossof water and low water use efficiency. Appropriate water pricing and strong political will towardsstrict compliance of rules & regulation for recovery of at least cost of operations and maintenanceof water delivery systems are needed for sustainable water management in India. Presently thereis no provision to price irrigation water on a volumetric basis, and irrigation water charges arenegligible. Irrigation water should be supplied on a volumetric basis, and water pricing should beon a national basis. Studies on the urban water supply of a few big cities indicate better pricing ofdomestic and industrial water supplies as compared to irrigation water. Groundwater extractionshould also be charged adequately to check overexploitation. Virtual water of agriculturalproducts and water footprint should also be considered for crop diversification and export/importof agricultural products.